Comparison of Mean Pain Score with Inguinal Block under Gen. Anes. versus Subarachnoid Block in Adult Pts UIH - Sheikh Ziarat Ali, Waqas Aziz, Kiran Qamar, Fariha Aslam, Mehtab Tipu Chaudary, Nazia Rubab Maqbool (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the mean pain score with inguinal block under general anesthesia versus subarachnoid block in adult patients undergoing inguinal hernioplasty. Design of the Study: Randomized controlled trial Study Settings: This cross-sectional study was conducted at Department of Anesthesiology, Sir Ganga Ram Hospital, Lahore from January 2021 to June 2021. Materials and Methods: Sample of 200 cases was included through non probability purposive sampling. In group A, patients were given inguinal block and in group B, patients were given subarachnoid block. In Inguinal block group, a 10mL of Bupivacaine (0.5%) will be given at junction of 2/3 form umbilicus and 1/3 from anterior superior iliac spine after administration of general anesthesia with laryngeal mask airway. Patients were followed at 1, 2 and finally on 4 hours after surgery for measurement of pain. Results: The mean age of 39.63±6.50 years. Out of total 200 patients, 186 (93%) were males and 14 (7%) were females. The mean pain score at 1st hour in inguinal group was 0.76±0.87 whereas pain score in Subarachnoid block was 1.18±0.92. Similarly after 2nd hour inguinal group pain score was 0.88±0.84 and with Subarachnoid block was 1.33±1.04. At 3rd hour, with inguinal block mean pain score was 1.02±0.92 and with Subarachnoid block was 1.80±1.20. At 4th hour, with inguinal block mean pain score was 1.59±1.07 and with Subarachnoid block was 3.09±1.60. Statistically there is highly significant difference of mean pain score between both groups i.e. p-value<0.05. There was drastic increase in mean main score at 4th hour with subarachnoid block as compared to inguinal block showing that inguinal block is more effective in reducing pain after 4 hours of surgery. Conclusion: It was concluded from results of this study that inguinal block is more beneficial in controlling pain after inguinal hernia surgery as compared to subarachnoid block